Analisis Semiotika Roland Barthes dalam Novel Istri Kedua Karya Asma Nadia dan Isa Alamsyah - Nana Jamilatu Rohmah (Journal of Communication Studies, 2022)
Preaching is one of the obligations for Muslims. There are various ways to preach or convey Islamic teachings in accordance with the Qur'an and As-Sunnah. One of them is the contemporary method, namely by using and following current technological developments, one of which is the bil-qalam media or written media such as literary works in the form of novels. One of them is the novel Second Wives by Asma Nadia and Isa Alamsyah which tells the true story of polygamous marriage and the consequences of being a second woman. In addition, there are also da'wah messages that can be used as lessons for life in the future. This study uses a qualitative research method with Roland Barthes' Semiotics approach. The source of this research data comes from primary data obtained from the print of the novel Second Wife with data collection techniques in the form of observation, collecting and documentation. The results of this study indicate that the novel Istri Second by Asma Nadia provides a clear picture both in denotation, connotation and myth about the message of da'wah contained in the novel Istri Second. da'wah message about the wisdom of a polygamous marriage and interfaith marriage. Married couples who abuse the meaning of polygamous marriage and interfaith marriage. Islam and state laws allow men to practice polygamy on the condition that they can act fairly and are able to provide for their wives and children physically and mentally. And in Islam and the law on marriage prohibits interfaith marriages because they are considered invalid. In a marriage there is a responsibility that must be carried out as a parent, namely nurturing and educating their children. Even though one day there is a divorce, the children are still the responsibility of their parents until they reach adulthood. And as children, we must obey and respect our parents because the pleasure of Allah lies in the pleasure of the parents, and the wrath of Allah lies in the wrath of the parents.